Diatom-based inferences of environmental changes from an alpine lake on the southeast edge of the Tibetan plateau over the last 4000 years - Zhang, Yunxia; Peng, Wei; Li, Yanling; Xiao, Xiayun; Hillman, Aubrey (Frontiers in Earth Science, 2024)
To better understand how global and regional-scale climate has changed, high-resolution records for environmental changes are still needed in southwestern (SW) China during the Late Holocene epoch. This study presents a well-dated high-resolution diatom analysis from a 1.66-m-long sediment core taken from Lake Cuogeda (CGD) on the southeast (SE) edge of the Tibetan Plateau to document environmental changes over the past ~4000 years. Diatom and other geochemical proxies show that, from 3850 to 3430 cal yr BP (before present, 0 BP=1950 AD, 1900 to 1480 BC), the environment of Lake CGD is acidic, oligotrophic, and enriched with humic acids. And the lake ice cover duration is short during this period. During 3430-1550 cal yr BP (1480 BC-400 AD), Lake CGD has less humic acid and a relatively high pH environment. The ice cover duration is longer, and the temperature drops during this period. Our multi-indicator recorded two environment fluctuations at ~2800 cal yr BP (850 BC) and 2210-1950 cal yr BP (260 BC-0 AD).